2012
DOI: 10.7439/ijbar.v3i2.232
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of Ultradeformable Soft Elastic Nano Vesicle Ethosomes for Dermal Delivery

Abstract: Clotrimazole is an antifungal drug for treatment of cutaneous candidiasis infections. However its oral administration is associated with number of drawbacks. The goal of the current investigation is to evaluate the transdermal potential of novel vesicular carrier, ethosomes, bearing Clotrimazole an antifungal having limited transdermal permeation. Clotrimazole loaded ethosomes were prepared, optimized and characterized for vesicular shape and surface morphology, vesicular size, size distribution, entrapment ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The resulting shape resembles the shape of ethosomes from the previous study, unilamellar and spherical. 16 Particle Size Distribution, Polydispersity Index, and Zeta Potential…”
Section: Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting shape resembles the shape of ethosomes from the previous study, unilamellar and spherical. 16 Particle Size Distribution, Polydispersity Index, and Zeta Potential…”
Section: Morphologymentioning
confidence: 99%
“…A sample of 1.0 g was applied to the skin surface. Then, at several time intervals (2,4,6,8,10,12,14,16,18,20, and 24 h) samples (3.0 mL) was taken from receptor compartment using a syringe and receptor compartment was refilled with the same amount of phosphate buffer pH 5.5. Next, the sample was inserted into the vial and its concentration measured by TLC-densitometry.…”
Section: In Vitro Penetration Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashitaba leaf phytoconstituents such as chalcone and coumarin act as antibacterial and anti-inflammatory, Increased penetration of ashitaba leaf nanoparticles in ethosomal gel occurs by various mechanisms. Nano ethosomal, which is smaller than 300 nm, can pass through the skin membrane to the deepest layers (Samnani et al, 2012). The ethanol and propylene glycol content in nano ethosomal increases transdermal penetration and causes drug interactions with stratum corneum lipid molecules (Zhou et al, 2018), this will increase the fluidity of the lipid bilayer and lead to an increase in stratum corneum permeability to drugs (Bendas and Tadros 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Research on calcitonin showed evidence of this claim ( 16 ). For the treatment of cutaneous fungal infections, permeation of the selected drug into the deeper layers of the skin is necessary ( 17 ). The small size of the lipid nano particles improves the presence of nano particles in direct contact with stratum corneum and ensures entry of the encapsulated drugs into the skin ( 18 ).…”
Section: Discussionmentioning
confidence: 99%